PERAN KEPALA SEKOLAH/MADRASAH PEREMPUAN DALAM MENGEMBANGKAN BUDAYA LITERASI - Rusydiyah, Evi Fatimatur (Islamuna: Jurnal Studi Islam, 2017)
Schools/madrasahs have a vital role in cultural transition. The role is very significant in changing the culture of society through the next generation of Indonesian people who are still sitting in school. This role can not be separated from the managerial aspect of principal in supporting the reading culture program in schools/madrasahs. This study focuses on: (1) how is the application of literacy culture in schools/madrasah headed by women?; (2) how is the special program of cultural literacy development implemented in schools/madrasahs that have women principals? The writing is a qualitative descriptive research.